2000
DOI: 10.1046/j.1469-0705.2000.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cerebral blood flow redistribution in late gestation: identification of compromise in small fetuses with normal umbilical artery Doppler

Abstract: MCA Doppler may be a useful tool to assess the health of small fetuses in the late third trimester. Redistribution may occur in the presence of normal umbilical artery Doppler and should be suspected when the HC/AC ratio is elevated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(182 citation statements)
references
References 23 publications
(21 reference statements)
7
169
0
6
Order By: Relevance
“…In FGR, as the umbilical artery Pi is increased, and the MCA PI may be reduced, the CPR is low. Fetal brain sparing (low MCA PI or CPR) has been associated with adverse pregnancy outcomes, even in fetuses with normal umbilical artery Doppler [45,49]. However, the CPR improves the prediction of adverse pregnancy outcomes when compared to its individual components [49][50][51][52][53].…”
Section: Fetal Dopplermentioning
confidence: 99%
See 1 more Smart Citation
“…In FGR, as the umbilical artery Pi is increased, and the MCA PI may be reduced, the CPR is low. Fetal brain sparing (low MCA PI or CPR) has been associated with adverse pregnancy outcomes, even in fetuses with normal umbilical artery Doppler [45,49]. However, the CPR improves the prediction of adverse pregnancy outcomes when compared to its individual components [49][50][51][52][53].…”
Section: Fetal Dopplermentioning
confidence: 99%
“…Fetal brain sparing (low MCA PI or CPR) has been associated with adverse pregnancy outcomes, even in fetuses with normal umbilical artery Doppler [45,49]. However, the CPR improves the prediction of adverse pregnancy outcomes when compared to its individual components [49][50][51][52][53]. It has been shown that a suboptimal or low CPR is associated with short-term markers of neonatal outcome such as cord blood acidemia, need for emergency operative delivery and neonatal unit admission [54][55][56][57], as well as stillbirth and neonatal morbidity [48,[57][58][59].…”
Section: Fetal Dopplermentioning
confidence: 99%
“…Furthermore, this sequential deterioration can rarely be observed beyond 32-34 weeks of gestation. After this period, the fetal growth asymmetry and the brain sparing effect can be the only evidence of placental insufficiency and fetal hypoxia (32)(33)(34), which implies that the hemodynamic indicators of fetal distress should be searched for in the fetal cerebral circulation.…”
Section: Introductionmentioning
confidence: 99%
“…MCA may be valuable for the identification of adverse outcome among late-onset FGR though its role in prediction is weak, independently of umbilical artery Doppler, which is often normal in these fetuses [69][70][71]. The cerebroplacental ratio (CPR) quantifies the redistribution of cardiac output by dividing the Doppler indices of the middle cerebral artery (MCA) with that of the umbilical artery.…”
Section: Middle Cerebral Artery Dopplermentioning
confidence: 99%